1973
DOI: 10.1084/jem.138.2.342
|View full text |Cite
|
Sign up to set email alerts
|

CELLULAR MEDIATORS OF ANTI-LISTERIA IMMUNITY AS AN ENLARGED POPULATION OF SHORT-LIVED, REPLICATING T CELLS

Abstract: An intravenous immunizing infection with the facultative, intracellular parasite, Listeria monocytogenes results in the production in the spleen of a population of immunologically-committed lymphocytes which can adoptively immunize normal recipients against a lethal challenge infection. These cellular mediators of immunity are first produced in the spleen between days 2 and 4 of infection and reach peak production on day 6. Their production then progressively decreases until about day 20 when their presence ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
137
0

Year Published

1974
1974
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 203 publications
(142 citation statements)
references
References 18 publications
(16 reference statements)
5
137
0
Order By: Relevance
“…In the context of ⌬actA L. monocytogenes infection, the magnitude of infection and the length of Ag display had little effect upon the timing of CD8 ϩ -T-cell contraction (4). However, in virulent L. monocytogenes infection, the infection was prolonged and the peak of the CD8 ϩ -T-cell response was delayed compared to reports of attenuated L. monocytogenes infection (4,10,14,16,29,34,52). One potential explanation for this discrepancy was that the timing of the peak of infection had more influence upon the onset of T-cell contraction than the total length of Ag display.…”
Section: Discussionmentioning
confidence: 45%
See 1 more Smart Citation
“…In the context of ⌬actA L. monocytogenes infection, the magnitude of infection and the length of Ag display had little effect upon the timing of CD8 ϩ -T-cell contraction (4). However, in virulent L. monocytogenes infection, the infection was prolonged and the peak of the CD8 ϩ -T-cell response was delayed compared to reports of attenuated L. monocytogenes infection (4,10,14,16,29,34,52). One potential explanation for this discrepancy was that the timing of the peak of infection had more influence upon the onset of T-cell contraction than the total length of Ag display.…”
Section: Discussionmentioning
confidence: 45%
“…One difference between virulent and ⌬actA L. monocytogenes infections is the time course of infection (14,16,29,34,52). Thus, we hypothesized that these differences in infection kinetics lead to differences in Ag presentation and the timing of CD8…”
Section: The Cd8mentioning
confidence: 99%
“…Vaccines utilizing inactivated or recombinant bacteria have been demonstrated to elicit both CD4-and CD8-T-cell activation (16), but they seem to be inefficient stimulators of effector (25) and memory (34) T cells if compared side by side with live bacteria (25) or recombinant viral vaccines (34). In this respect, inactivated intracellular bacterial vaccines are similar to natural M. tuberculosis (44) and L. monocytogenes (33) infections, which fail to induce sufficient immunological memory to prevent recurrent infections. DNA vaccines have been demonstrated to induce protection against infections with M. tuberculosis (43) and L. monocytogenes (9).…”
Section: Major Histocompatibility Complex (Mhc) Class I-restricted Cd8mentioning
confidence: 99%
“…Mice infected with Listeria mount an ␣␤ T cell-mediated adaptive immune response that is only first weakly detectable on the third day of infection (43). The detrimental effect of removing V␥1 ϩ cells during a Listeria infection at an early time point thus suggested that they primarily influence components of the innate immune response.…”
Section: Depletion Of the V␥1mentioning
confidence: 99%